209k views
4 votes
If -y-2x^3=Y^2 then find D^2y/dx^2 at the point (-1,-2) in simplest form

^^ the main problem i am having is when I have to use the quotient rule

User Neige
by
4.6k points

1 Answer

7 votes

Answer:


(d^2y)/(dx^2) = (-4)/(3)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Factoring

Calculus

Implicit Differentiation

The derivative of a constant is equal to 0

Basic Power Rule:

  • f(x) = cxⁿ
  • f’(x) = c·nxⁿ⁻¹

Product Rule:
(d)/(dx) [f(x)g(x)]=f'(x)g(x) + g'(x)f(x)

Chain Rule:
(d)/(dx)[f(g(x))] =f'(g(x)) \cdot g'(x)

Quotient Rule:
(d)/(dx) [(f(x))/(g(x)) ]=(g(x)f'(x)-g'(x)f(x))/(g^2(x))

Explanation:

Step 1: Define

-y - 2x³ = y²

Rate of change of tangent line at point (-1, -2)

Step 2: Differentiate Pt. 1

Find 1st Derivative

  1. Implicit Differentiation [Basic Power Rule]:
    -y'-6x^2=2yy'
  2. [Algebra] Isolate y' terms:
    -6x^2=2yy'+y'
  3. [Algebra] Factor y':
    -6x^2=y'(2y+1)
  4. [Algebra] Isolate y':
    (-6x^2)/((2y+1))=y'
  5. [Algebra] Rewrite:
    y' = (-6x^2)/((2y+1))

Step 3: Differentiate Pt. 2

Find 2nd Derivative

  1. Differentiate [Quotient Rule/Basic Power Rule]:
    y'' = (-12x(2y+1)+6x^2(2y'))/((2y+1)^2)
  2. [Derivative] Simplify:
    y'' = (-24xy-12x+12x^2y')/((2y+1)^2)
  3. [Derivative] Back-Substitute y':
    y'' = (-24xy-12x+12x^2((-6x^2)/(2y+1) ))/((2y+1)^2)
  4. [Derivative] Simplify:
    y'' = (-24xy-12x-(72x^4)/(2y+1) )/((2y+1)^2)

Step 4: Find Slope at Given Point

  1. [Algebra] Substitute in x and y:
    y''(-1,-2) = (-24(-1)(-2)-12(-1)-(72(-1)^4)/(2(-2)+1) )/((2(-2)+1)^2)
  2. [Pre-Algebra] Exponents:
    y''(-1,-2) = (-24(-1)(-2)-12(-1)-(72(1))/(2(-2)+1) )/((2(-2)+1)^2)
  3. [Pre-Algebra] Multiply:
    y''(-1,-2) = (-48+12-(72)/(-4+1) )/((-4+1)^2)
  4. [Pre-Algebra] Add:
    y''(-1,-2) = (-36-(72)/(-3) )/((-3)^2)
  5. [Pre-Algebra] Exponents:
    y''(-1,-2) = (-36-(72)/(-3) )/(9)
  6. [Pre-Algebra] Divide:
    y''(-1,-2) = (-36+24 )/(9)
  7. [Pre-Algebra] Add:
    y''(-1,-2) = (-12)/(9)
  8. [Pre-Algebra] Simplify:
    y''(-1,-2) = (-4)/(3)
User Marcelus Trojahn
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.